Research handbook on entrepreneurship as practice - Thomson, Neil A.; Byrne, Orla; Jenkins, Anna; Teague, Bruce T. (Handbooks of business and management research as practice series, 2022)
"This Research Handbook advances entrepreneurship theory in new ways by integrating and contributing to contemporary theories of practice. Leading practice theorists and entrepreneurship experts, who are part of the growing Entrepreneurship as Practice -EaP- research community, expertly propose methodologies, theories and empirical insights into the constitution and consequences of entrepreneuring practices. This comprehensive Research Handbook pushes boundaries in scholarship about what entrepreneurship is and what it can become. It is split into four parts covering new foundations, new theoretical advances and methodological advances. Together, with an insightful Foreword by William B. Gartner, chapters examine insights into the nature and consequences of entrepreneurship, its practices and relations, as well as novel research methods for conducting empirical EaP research. Collectively, this Handbook marks a bright future for EaP research. This insightful Research Handbook will provide an excellent up-to-date introduction to EaP research for entrepreneurship, management and organization scholars as well as scholars new to theories of practice. Practitioners and researchers will also benefit from the wider perspective that this book provides in a novel, exciting and powerful way to fully understand entrepreneurship"--